Improving germination of aged melon seed using garlic oil emulsion - April Lia Sahidah; Anung Wahyudi; Ni Siluh Putu Nuryanti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Seed storage is an important aspect of plant breeding. Aged seeds tend to lose their viability during storage, reducing their ability to grow. One effort to increase the viability of seed germination that has been stored for a long period is to provide priming treatment to the seeds before planting. The purpose of this study was to evaluate the effect of garlic oil emulsion on the germination of aged melon seed that has been stored for more than five years. The study was conducted using a factorial completely randomized design (CRD). The first factor consisted of two melon seed lines that had been stored for more than five years, namely Ougan makuwauri (V1) and Ginsen makuwauri (V2), and the second factor was the priming treatment consisting of P0 = Aquadest, P1 = 0.125% garlic oil emulsion, P2 = 0.25% garlic oil emulsion, and P3 = 0.5% garlic oil emulsion, each treatment was repeated three times with a soaking time of 20 hours. There is an interaction between the line and priming treatment that significantly affects the variable of cotyledon opening on the fifth day and hypocotyl length. Meanwhile, the single priming treatment has a significant effect on the observation variable of cotyledon opening on the third day and has a very significant effect on the variable of root length of germinated melon seeds. Keywords: Ginsen makuwauri; old seeds; Ougan makuwauri; priming treatment